Google Forms: An Assessment Tool Accommodating the Generation-Z Students’ Learning Needs - Citra Suryanovika (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
Abstract. The study employed qualitative approach because the data were students’ responses on Google Forms, and students’ midterm score. It was aimed to exploring the use of Google forms in assessing students’ knowledge of the materials of Introduction to Linguistics. The materials were given until the sixth meetings in the Odd Semester of 2019/2020 were linguistics, the phonological term, pronunciation of certain words, the morphological formation and construction. Eleven questions on  Google forms were in multiple choice, checkbox, multiple choice/checkbox grid, and short answer. The study has found that most of the students in Class A and Class B firstly used Google forms as the assessment tool with duration was set. Google form is useful for the teacher and students because it provides automatic calculation which enables effective and efficient feedback for the students to learn their mistakes. The study also found that auto grading on Google forms only calculates the correct answers which marked in the answer key feature. Thus, it would be suitable for grading questions in multiple choice and multiple choice grid, questions in checkboxes, short answer, and checkbox grid still needs manual grading. After comparing the score of assessment on Google Forms and midterm test, it can be concluded that students’ score was improved significantly after the assessment.Keywords: Google Forms, assessment, generation-Z, students’ learning needsAbstrak. Penelitian in imenggunakan pendekatan kualitatif mengingat data yang digunakan adalah respon mahasiswa dari Google Form, dan nilai Ujian Tengah Semester Mahasiswa. Penelitian ini bertujuan untuk mengetahui penggunaan Google form dalam menial pengetahuan mahasiswa akan materi mata kuliah Introduction to Linguistics. Materi-materi yang siberian hinge minggu keenam di Semester Ganjil than ajaran 2019/2020 adalah linguistik, istilah fonologi, pengucapan kata-kata tertentu, pembentukan dan konstruksi morfologis. Sebelas pertanyaan di Google Forms dalam bentuk pilihan ganda, kotak centang, kisi pilihan ganda/kotak centang, dan jawaban singkat. Penelitian ini telah menemukan bahwa sebagian besar mahasiswa Kelas A dan Kelas B baru pertama kali menggunakan Google Forms sebagai alat penilaian dengan durasi yang telah ditetapkan. Pada praktinya, Google Forms berguna bagi dosen dan mahasiswa karena adanya penghitungan otomatis yang memungkinkan umpan balik yang efektif dan efisien kepada mahasiswa untuk mempelajari kekeliruan mereka.Penelitian ini juga menemukan bahwa penilaian otomatis Google Forms hanya menghitung jawaban benar yang ditandai di figure kunci jawaban. Sehingga, penghitungan nilai hanya berlaku pada sol dengan pilihan ganda dan kisi pilihan ganda, penghitungan nilai secara manual masih harus dilakukan pada sol dalam bentuk kotak centang, kisi kotak centang dan jawaban singkat. Setelah membandingkan nilai pada Google Forms dan Ujian Tengah Semester, ditemukan bahwa nilai mahasiswa meningskat cukup signifikan setelah penilaian dengan Google Forms.Kata kunci: Google Forms, penilaian, generasi-Z, kebutuhan pembelajaran mahasiswa.